Multimodal control of chronic pain and comorbidities with atypical analgesics – “two birds with one stone” - Stepanović-Petrović, Radica; Tomić, Maja; Jovanović, Aleksandar; Pecikoza, Uroš; Micov, Ana; Nastić, Katarina (Archives of Pharmacy, 2022)
Osteoarthritis (OA) is the most common rheumatic disease, affecting over 300 million people worldwide. It causes chronic pain, disability and is commonly associated with comorbid diseases (CMD) that cause worse health outcomes, more complex management, and increased healthcare costs. Current treatments (typical/atypical analgesics) have limited efficacy and/or tolerability and usually do not affect or can even worse CMD. In era of longer life expectancy, extended professional life and reduced pension funds in Serbia and Europe, there is a compelling need for maintaining functionality and working capability of older population. Our aim is to search for novel treatments that could concomitantly treat chronic pain and its major CMD: depression, cognitive impairment and/or cardiovascular disease (CVD). It was planned to test the effects of vortioxetine, a novel antidepressant with multimodal mechanism of action, on pain, depressive and cognitive-impairment behaviour and CV status in rat model of knee OA. Its effects will be compared to the effects of duloxetine, the only antidepressant used for pain relief in OA. Next, we will test the effects of 2-component combinations of vortioxetine/duloxetine with adjuvant treatments (regular exercise/metformin/nicotinamide), that showed the potential to alleviate pain, depression, reduced cognition and/or CVD in preclinical/clinical research. If proved effective and well tolerated, new treatment(s) could be implemented in clinical practice much faster and with significantly less investment, than those required to develop brand new drug, as they consist of drugs already approved for human use and safe, widely available and inexpensive non-pharmacologic measures.